Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/000313481808400857
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Ventral Hernia Repair after Open Abdominal Aortic Aneurysm and Open Aortofemoral or Aortoiliac Bypass Surgery: An Analysis of 17,594 Patients in the State of New York

Abstract: The purpose of our study was to evaluate the rate of ventral hernia repair (VHR) after open abdominal aortic anneurysm in New York State compared with the rate of VHR after open abdominal aortic bypass procedures. The Statewide Planning and Research Cooperative System database was queried for all abdominal aortic aneurysm (AAA) and bypass procedures performed between 2000 and 2010. Social security death index was used to identify patients who died. The cause-specific Cox proportional hazard model was applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Hernias develop more rapidly (within the first 24 month) in patients with AAAs than they do in those patients with aorto-iliac occlusive disease. 10,42 Previous studies have shown that the cumulative hernia incidence increases continuously for up to seven years after the operation, 4,38,43 suggesting that AAA patients should perhaps be followed for longer.…”
Section: Risk Ratio For Incisionalmentioning
confidence: 99%
“…Hernias develop more rapidly (within the first 24 month) in patients with AAAs than they do in those patients with aorto-iliac occlusive disease. 10,42 Previous studies have shown that the cumulative hernia incidence increases continuously for up to seven years after the operation, 4,38,43 suggesting that AAA patients should perhaps be followed for longer.…”
Section: Risk Ratio For Incisionalmentioning
confidence: 99%
“…In a study of 17,594 patients (9,314 with AAA and 8,280 with AOD) by Altieri et al,[ 19 ] after controlling for all other factors, patients undergoing AAA repair were more likely to undergo ventral hernia repair (7.93% with AAA and 5.8% with AOD). The authors concluded that prophylactic use of mesh might be considered in this patient population for future procedures due to their significant comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of association of IH after midline laparotomy in collagen disease patients related to abdominal aortic aneurism (AAA) has been widely demonstrated in studies of high scientific evidence (30)(31)(32). In this scenario, IH can reach up to 30%-60%.…”
Section: Collagen Diseases (Abdominal Aortic Aneurism)mentioning
confidence: 99%